Long persuasion games - Françoise Forges; Frédéric Koessler (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper characterizes geometrically the set of all Nash equilibrium payoffs achievable with unmediated communication in persuasion games, i.e., games with an informed expert and an uninformed decisionmaker in which the expert's information is certifiable. The first equilibrium characterization is provided for unilateral persuasion games, and the second for multistage, bilateral persuasion games. As in Aumann and Hart (2003), we use the concepts of diconvexification and dimartingale. A leading example illustrates both geometric characterizations and shows how the expert, whatever his type, can increase his equilibrium payoff compared to all equilibria of the unilateral persuasion game by delaying information certification.
Keywords: D82; C72; 330; cheap talk; communication; diconvexification; dimartingale; disclosure of certifiable information; jointly controlled lotteries; Nichtkooperatives Spiel; Kommunikation; Asymmetrische Information; Dynamisches Spiel; Nash-Gleichgewicht; Theorie; cheap talk